Exercise systolic blood pressure at moderate workload predicts cardiovascular disease and mortality through 35 years of follow-up in healthy, middle-aged men. (4th July 2017) - Mariampillai, Julian E.; Engeseth, Kristian; Kjeldsen, Sverre E.; Grundvold, Irene; Liestøl, Knut; Erikssen, Gunnar; Erikssen, Jan; Bodegard, Johan; Skretteberg, Per Torger
Abstract: Objective: There is an association between exercise systolic blood pressure (SBP) and cardiovascular disease and mortality. The aim of this study was to investigate this association, with 35 years of follow-up. Methods: Through 1972–75, 2014 healthy, middle-aged men underwent thorough medical examination and a bicycle exercise test. 1999 participants completed six minutes at 100 W. SBP was measured manually, both before the test and every two minutes during the test. Highest SBP measured during the first six minutes (SBP100W) was used in further analyses. Results: Participants were divided into quartiles (Q) based on their SBP100W; Q1: 100–160 mm Hg ( n  = 457), Q2: 165–175 mm Hg ( n  = 508), Q3: 180–195 mm Hg ( n  = 545) and Q4: 200–275 mm Hg ( n  = 489). After 35-years follow-up, there was a significant association between exercise SBP at baseline and cardiovascular disease and mortality. In the multivariate analysis adjusting for resting SBP, age, smoking status, total serum cholesterol and family history of coronary heart disease, as well as physical fitness, there is a 1.39-fold (CI: 1.00–1.93, p  = 0.05) increased risk of cardiovascular mortality in Q4 compared to Q1. When not adjusting for physical fitness, there is a 1.29-fold (CI: 1.03–1.61, p  = 0.02) increase in risk of cardiovascular disease between Q1 and Q4. Conclusions: The results of this study suggest that the association between exercise SBP at moderate workload and cardiovascular disease and mortality in middle-aged men extends through as long as 35 years and into old ages.